Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1021/jo00401a030
|View full text |Cite
|
Sign up to set email alerts
|

Structures of some of the minor aminoglycoside factors of the nebramycin fermentation

Abstract: The structures of some of the minor factors of the nebramycin complex of antibiotics are elucidated through a combination of physical and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Inspection of the data in Table 1 reveals a ÁH b of À2.2 kcal/mol at pH 5.5. Note that tobramycin is essentially 100 % protonated at this pH (Dorman et al, 1976;Koch et al, 1978). Thus, our observed binding enthalpy at pH 5.5 (À2.2 kcal/mol) re¯ects the intrinsic heat associated with the binding of the pentacationic form of tobramycin to the host p(rI) Áp(rC) duplex.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Inspection of the data in Table 1 reveals a ÁH b of À2.2 kcal/mol at pH 5.5. Note that tobramycin is essentially 100 % protonated at this pH (Dorman et al, 1976;Koch et al, 1978). Thus, our observed binding enthalpy at pH 5.5 (À2.2 kcal/mol) re¯ects the intrinsic heat associated with the binding of the pentacationic form of tobramycin to the host p(rI) Áp(rC) duplex.…”
Section: Resultsmentioning
confidence: 66%
“…The structure of tobramycin in which the atomic and ring numbering systems are denoted in Arabic and Roman numerals, respectively. The NMRderived (Dorman et al, 1976;Koch et al, 1978) pK a values of the ®ve amino groups are indicated.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a few sugars highlighted in the previous paragraph found appended at C-6 of aminoglycoside core aglycons ( 2 , 4 , 8 , 10 , 12 ), 54,62,63 additional sugar diversity has been found at C-6 including: α-D-glucose ( 18 ); 64 3′-amino-3′-deoxy-α-D-xylose 21 (gentamicins and sisomicins) 37,65 and its C-4′-methyl branched 19 (prevalent in a range of aminoglycosides); 51,66,67 C-4′-methyl branched 3′-amino-3′-deoxy-α-D-galactose 20 (combimicins); 56 3′-amino-3′-deoxy-β-L-arabinose ( 22 , gentamicins and related compounds); 37,65 2′-amino-2′-deoxy-α-D-xylose 24 and its corresponding 2′,3′-diamino-2′,3′-dideoxy analog 23 (seldomycins); 58,68 as well as 3′-amino-3′-deoxy-β-D-mannose ( 42 ) and the diasaccharide I [comprised of the uniquely C-6′ oxidized mannose 43 and 2′-amino-2′-deoxy-α-D-xylose ( 24 ) in boholmycin]. 50 Other C-6′-appended sugars include L-streptose ( 28 ), 5′-hydroxy-L-streptose ( 30 ) and the corresponding reduced forms 29 and 31 have been found among streptomycins 6971 wherein further C-2′ glycosylation of the streptose moiety with 2′-amino-2′-deoxy-α-L-glucose ( 32 ) has been observed.…”
Section: Aminoglycosides and Related Secondary Metabolitesmentioning
confidence: 97%
“…The solution conditions for the AMP-PNP ITC experiments contained 10 mM buffer (Epps or Taps) at pH 8.0, 100 mM KCl, 5 mM MgCl 2 , and 0.01% TWEEN 80. 15 [21][22][23] Amino pK a values were determined from plots of the pH dependence of 15 N chemical shifts (δ) by non-linear least squared analyses using the following relationship:…”
Section: Isothermal Titration Calorimetry (Itc)mentioning
confidence: 99%